High rhizospheric ammonium levels in Sorghum halepense (johnsongrass) suggests nitrification inhibition potential - Eeshita Ghosh; Nithya Rajan; Dinesh Phuyal; Nithya Subramanian; Muthukumar Bagavathiannan (Agricultural & Environmental Letters)
Abstract Plants, such as sorghum (Sorghum bicolor), have been shown to secrete root exudates involved in biological nitrification inhibition (BNI), an ability to suppress the conversion of ammonium to nitrate and thereby minimize its loss. Johnsongrass (Sorghum halepense), a weedy relative of cultivated sorghum, may also possess BNI potential, but little is known in this regard. Here, we conducted a field survey at seven different sites in Southeast Texas to determine this evolutionary trait of johnsongrass in different soil environments. It was found that johnsongrass rhizosphere retains high levels (>60%) of ammonium within the total available N (ammonium + nitrate). Furthermore, the degree of ammonium retention by johnsongrass rhizosphere was significantly greater (up to 40%) in the roadside habitat compared to cultivated fields. The high ammonium retention potential by johnsongrass may explain, in part, their persistence and dominance, especially in marginal environments. Core Ideas Nitrogen is a limiting nutrient for plant growth, and nitrification causes loss of nitrogen. Ammonium retention was higher in roadside johnsongrass biotypes compared to that of cropland biotypes. The high rhizoshpheric ammonium retention by johnsongrass may explain, at least in part, its invasiveness. This trait could be further investigated and integrated into modern sorghum cultivars.